A study on the relationship between credit card usage, loans for properties and income level towards household debt in Malaysia / Mohammad Hazim Azmi - Azmi, Mohammad Hazim (2016)
Household debt has rapidly rises as major types of economic problems. All developed and developing countries are facing this economic problem since twentieth century. This economic problem not only affect developed nation such as United States of America, Japan and European Union but also developing nation including Malaysia. The objective of this research is to study on the relationship between credit card usage, loans for properties and income level towards household debt in Malaysia. This research also will investigate what is the most significant relationship between credit card usage, loans for properties and income level towards household debt in Malaysia. 60 individuals are being chosen as the respondent in this research by using the sample random sampling method. This research was using primary data as the questionnaire which is self-administered from early research was distributed to the target respondent. In order to analyze the primary data, the researcher use SPSS method to know the demographic profile, descriptive analysis, reliability analysis, correlation analysis and the regression analysis. By using the SPSS method, it is proven that variable credit card usage and income level has significant relationship with the household debt in Malaysia while variable loans for properties will not influence the household debt in Malaysia. In order to get a better and accurate result, future researcher should include other factors which might affect the household debt in Malaysia such as attitude toward money and consumer credit